Effects of different living conditions on the risk of osteoporosis in Chinese community-dwelling elderly: a 3-year cohort study. Issue 8 (August 2020) - Yu, Xing; Zhang, Yuanyuan; Han, Peipei; Fu, Liyuan; Chen, Xiaoyu; Hou, Lin; Song, Peiyu; Zhao, Yong; Guo, Qi
Objective: Osteoporosis can lead to bone fragility and an increased risk of bone fracture with resultant high morbidity and mortality. Living alone has been associated with various mental and physical health problems. However, the risk of osteoporosis among individuals with different living conditions and changing living conditions is unclear. We examined the risk of osteoporosis in different living conditions over a 3-year period in community-dwelling suburban elderly Chinese. Methods: This study involved 288 elderly Chinese suburb-dwelling participants with no documented history of osteoporosis. All were aged ≥60 years (mean, 65.6±3.75 years; 157 men). A quantitative ultrasound scan of the calcaneus with a T score of <−2.5 was used to identify a high risk of osteoporosis. Results: In total, 54.2% of participants were determined to have a high risk of osteoporosis (male, 51.6%; female, 57.3%). People who had always lived alone had a significantly higher risk of osteoporosis, even after adjusting for potential confounders. A change from living alone to living with others had no significant impact on the risk of osteoporosis. Conclusion: Our results indicate that living alone is associated with a high risk of osteoporosis. Thus, people who live alone may need regular bone tests to avoid adverse events.